The glass closet : why coming out is good business - Browne, John, 1948- (New York : Harper Business, 2014)
Exposing the culture of homophobia that still runs rampant in corporations around the world, the former CEO of BP draws on his own experiences to reveal why self-disclosure is best for employees despite the risk.
Includes bibliographical references (pages 203-234) and index.
Keywords: Browne, John, -- 1948-; British Petroleum Company; Homosexuality in the workplace; Gay executives -- Great Britain -- Biography